Consideration of structural ageing in the development of analytical fragility functions - Çevik, Onur. (Thesis (M.S.) - Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2023., 2023)
This study investigates the ageing effects led by the corrosion of structural materials on the fragility functions analytically derived for reinforced concrete momentresisting frame type buildings which is the predominant typology in T¨urkiye. First, in situ and laboratory material testing results for 175 reinforced concrete buildings located in Istanbul, constructed between 1962 and 2004 with different heights and plan features are examined in order to better understand the level of corrosion and its spread in structural members. The level of corrosion and different ways it occurs is then implemented in structural analyses by altering the mechanical properties and constitutive models of materials with the data obtained from the experimental and numerical results in the literature. For this purpose, three-dimensional finite element models for lowand mid-rise buildings designed in accordance with the provisions of the 1975, 1997 and 2018 Turkish earthquake codes are elaborated. The responses of pristine and aged buildings are studied through nonlinear dynamic analyses under strong ground motion acceleration recordings selected and scaled to represent the level of seismic hazard in Istanbul. Multiple- stripe analysis and maximum likelihood method are implemented for the derivation of fragility functions. The results show that the behavior of structures aged by the effects of corrosion is a significant reduction in structural capacity and thus yields higher damage probability estimates by the derived fragility curves.
Keywords: Buildings, Reinforced concrete -- Earthquake effects.; Mechanics, Analytic.